Investigation of the impact of increased size and volume of encapsulation for long-term fouling control - Ralston, Emily; Pringle, Samantha (Frontiers in Marine Science, 2024)
Biofouling is a major concern for anthropogenic structures in terms of fuel costs, maintenance and environmental concerns with greenhouse gas emissions and transport of nonindigenous species. Antifouling coatings do not effectively protect many structures and niche areas. Encapsulation has been introduced as a potential long-lasting solution to prevent macrofouling. This study aims to determine the applicability of encapsulation for complex structures that cannot be wrapped with a tight-fitting bag. An experiment was designed to test the impact of different volumes and sizes of bags on the efficacy and life span of protection. Encapsulation within one and two-foot-diameter bags prevented macrofouling on inert PVC and bronze surfaces for the entire 12-month experiment. Fourfoot diameter bags prevented macrofouling on inert PVC surfaces for 8 months and bronze surfaces for 9 months. Regardless of bag size, a decrease in dissolved oxygen was observed within all bags compared to open water readings, which may play a role in decreased settlement on encapsulated surfaces.This method has proven effective for extended periods despite large enclosed volumes of water.